Prise en compte du développement durable dans l'evaluation des projets: Un point de vue français - Emile Quinet (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2013)
– Factoring sustainable development into the appraisal of investment projects is a topical issue at both the analytical and the decision-making level. In the area of analysis, we find numerous studies and research projects devoted to the assessment of environmental damage and its translation into monetary terms. The analysis concerns both 'flow' damage such as pollution and noise, and 'stock' damage with long-term cumulative effect, such as global warming and the reduction of biodiversity. In the area of decisionmaking, efforts are being undertaken in many countries to achieve better integration of these concerns in project appraisal and the related cost-benefit analysis. France is no exception: a working party recently set up to revise the methodology for appraising public investment projects has just completed its deliberations. It paid close attention to considerations of sustainable development and the factoring of the long term, and the present paper is based largely on its recommendations. In what follows, we shall endeavour to analyse those recommendations in the light of scientific knowledge and place them in the French institutional and politico-administrative context. The present paper begins with an overall presentation of the working party's deliberations. It goes on to discuss factoring the long term and one of its key characteristics, uncertainty. That is followed by a discussion of the two major aspects of stock effects, namely global warming - including the issue of carbon cost - and biodiversity. Finally, the paper discusses flow effects - the classical effects of air pollution and noise - and numerous other effects that are less clearly defined. It concludes with an overview of the impact of the new provisions on the choice of projects.
Keywords: 330; Infrastrukturinvestition; Projektmanagement; Nachhaltige Entwicklung; Kosten-Nutzen-Analyse; Frankreich